Elemental, morphological and thermal analysis of mixed microalgae species from drain water - Hossain N.; Zaini J.; Mahlia T.M.I.; Azad A.K. (Elsevier Ltd, 2023)
Algae; Bituminous coal; Calorimeters; Carbon; Coking properties; Microorganisms; Scanning electron microscopy; Thermoanalysis; Bio-energy; Coal blends; Large-scale applications; Scanning electron micrographs; Secondary electron images; SEM-EDX; Stigonematales sp; Thermogravimetric analyzers; Thermogravimetric analysis; bioenergy; chemical element; drain; instrumentation; microalga; morphology; scanning electron microscopy; thermogravimetry; Stigonematales